Elderly healthy class: Health education program recognizing cardiorespiratory problems - Alinda Nur Ramadhani; Dea Linia Romadhoni (Universitas Muhammadiyah Magelang, 2023)
The elderly experience a decrease in body systems, one of which is a decrease in the function of the cardiorespiratory system. There are three important things in the changes that occur in the aging process, namely the gradual increase in the size of the alveoli, the disintegration of the supporting structures of the lungs, and the weakening of respiratory muscles that occur in the aging process. The Elderly Healthy Class aims to develop, maintain and know the movements and functions of the body in the elderly, as well as the prevention of advanced disease in the elderly. The Elderly Healthy Class provides counseling on cases of cardiorespiratory, demonstration, exercises and checkup for the elderly. The results of the evaluation showed an increase in the knowledge of the elderly after attending the Elderly Healthy Class.